2022
DOI: 10.1080/0142159x.2022.2130038
|View full text |Cite
|
Sign up to set email alerts
|

Virtual interviewing for graduate medical education recruitment and selection: A BEME systematic review: BEME Guide No. 80

Abstract: Background: The COVID-19 pandemic caused graduate medical education (GME) programs to pivot to virtual interviews (VIs) for recruitment and selection. This systematic review synthesizes the rapidly expanding evidence base on VIs, providing insights into preferred formats, strengths, and weaknesses. Methods: PubMed/MEDLINE, Scopus, ERIC, PsycINFO, MedEdPublish, and Google Scholar were searched from 1 January 2012 to 21 February 2022. Two authors independently screened titles, abstracts, full texts, performed da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 124 publications
1
12
0
Order By: Relevance
“…It is validating that many of our findings broadly align with what has been previously described in the literature about virtual interviews. A systematic review of virtual interviewing for graduate medical education recruitment and selection demonstrates similar findings: that virtual interviews pose challenges in assessing "fit," that applicants prefer three to five individual interviews lasting 15 to 20 minutes each, and that opportunities to connect with faculty and trainees are priorities for applicants (16). More specifically, multiple surveys have shown that fellowship applicants are interested in hybridized approaches to interviewing in order to better understand program culture (17,18).…”
Section: Discussionmentioning
confidence: 89%
“…It is validating that many of our findings broadly align with what has been previously described in the literature about virtual interviews. A systematic review of virtual interviewing for graduate medical education recruitment and selection demonstrates similar findings: that virtual interviews pose challenges in assessing "fit," that applicants prefer three to five individual interviews lasting 15 to 20 minutes each, and that opportunities to connect with faculty and trainees are priorities for applicants (16). More specifically, multiple surveys have shown that fellowship applicants are interested in hybridized approaches to interviewing in order to better understand program culture (17,18).…”
Section: Discussionmentioning
confidence: 89%
“…As a side effect, we would expect these methods to be more accepted, which would subsequently lower interviewee stress and perception of suboptimal performance. This practical implication in terms of training is pressing given that these interview methods have become commonplace and especially with the COVID‐19 pandemic context (Constantin et al, 2021; Daniel et al, 2022; Roulin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…AVIs are receiving increased attention because they offer numerous advantages (Bauer et al, 2004; Daniel et al, 2022; Guchait et al, 2014; Langer et al, 2017; Lukacik et al, 2022; Roulin et al, 2022; Suen et al, 2019). For instance, these methods allow large‐scale interviewing because an unlimited number of interviews can be conducted at the same time, thus increasing an organization's chances of finding the best‐qualified applicant for a specific position.…”
Section: Introductionmentioning
confidence: 99%
“…Most applicants and programs supported the continued use of virtual interviews due to the significant cost and time savings, the potential to enhance equity, and a positive environmental impact. 12 A survey of internal medicine program directors (PDs) in March 2021 demonstrated that the majority (>80%) were satisfied with the incoming class of interns who interviewed virtually. Benefits included lower cost and easier recruitment of faculty interviewers, but many (82%) expressed concerns in demonstrating the esprit de corps of their programs and decreased ability in determining which applicants had sincere interest in their program (71%).…”
Section: Recruitment Into Rheumatologymentioning
confidence: 99%
“…Overall, satisfaction with virtual interviews was high; however, assessment of applicant and program “fit” was perceived as challenging by trainees and faculty. Most applicants and programs supported the continued use of virtual interviews due to the significant cost and time savings, the potential to enhance equity, and a positive environmental impact 12 . A survey of internal medicine program directors (PDs) in March 2021 demonstrated that the majority (>80%) were satisfied with the incoming class of interns who interviewed virtually.…”
Section: Introductionmentioning
confidence: 99%